Projeto de estrutura de fundação em concreto do tipo radier - Dória, Luís Eduardo Santos (2007)
This work presents some aspects related to geometry and rigidity classification and structural analysis of reinforced and prestressed concrete mat foundations. Some strategies for modeling and solving the structural system are discussed, with focus on grid analogy with elastic restraints and soil-structure interaction. Details of the computer aided design of mat foundations by grid analogy performed at CAD/TQS system are also presented. The material list and cost are investigated and compared for three real buildings considering two prestressed cable geometry: straight and parabolic. The results show that the prestressed concrete mat foundation gives thinner thickness and greater total cost. The former is due to increasing in concrete resistance and the last is due to additional rebars and multistrand cost. The prestressing cost was not considered.